2017
DOI: 10.1186/s12943-017-0633-8
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelin promotes epithelial-to-mesenchymal transition and tumorigenicity of human lung cancer and mesothelioma cells

Abstract: BackgroundLung cancer and pleural mesothelioma are two of the most deadly forms of cancer. The prognosis of lung cancer and mesothelioma is extremely poor due to limited treatment modalities and lack of understanding of the disease mechanisms. We have identified mesothelin as a potentially unique therapeutic target that as a specific advantage appears nonessential in most cell types. Mesothelin (MSLN), a plasma membrane differentiation antigen, is expressed at a high level in many human solid tumors, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 42 publications
3
65
0
Order By: Relevance
“…It is involved in important cellular processes, including cell adhesion, proliferation, invasion, and epithelial-to-mesenchymal transition. 18,19 Mesothelin is a glycophosphatidylinositol-linked membrane protein, but it also has three isoforms that are present in the circulation. 12,15,20 Enzyme-linked immunosorbent assay (ELISA) can detect different isoforms, usually referred to as soluble mesothelin related peptides (SMRP).…”
Section: Introductionmentioning
confidence: 99%
“…It is involved in important cellular processes, including cell adhesion, proliferation, invasion, and epithelial-to-mesenchymal transition. 18,19 Mesothelin is a glycophosphatidylinositol-linked membrane protein, but it also has three isoforms that are present in the circulation. 12,15,20 Enzyme-linked immunosorbent assay (ELISA) can detect different isoforms, usually referred to as soluble mesothelin related peptides (SMRP).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that EMT is associated with cell migration, invasion, and tumor progression; 3235 however, it remains controversial whether Slug acts as a tumor promoter or tumor suppressor based on recent reports. 36,37 Our previous studies showed that SWCNT-transformed cells exhibit aggressive cancer phenotypes, including increased cell migration, invasion, and anchorage-independent cell growth.…”
Section: Resultsmentioning
confidence: 99%
“…1C-D). Moreover, we also observed a clonal non-synonymous mutation in MSLN , a plasma membrane differentiation antigen which is emerging as an attractive target for cancer immunotherapy due to its potential involvement in the epithelial-to-mesenchymal transition, a cellular process thought to be required for metastatic dissemination 12 .…”
mentioning
confidence: 86%